Blockchain for Medical Research: Accelerating Trust in Healthcare, 1st edition - Manion, Sean T. (Productivity Press, 2020)
It takes 17 years on average to bring new medical treatments ideas into evidence-based clinical practice. The growing replicability crisis in science further delays these "new miracles." Blockchain can improve science and accelerate medical research while bringing a new layer of trust to healthcare.